Educational policies and the formation of future citizenship in Chile and Spain (1970-2016) (2021)
Objective: This article aims to comparatively study the Spanish and Chilean legislation (1970-2016) within the framework of citizenship education, in order to analyze the projects of the society of the future, as well as their main characteristics. Originality / contribution: this aspect of the discussion of the proposed analyses is considered relevant firstly because of the comparative nature of the work and, secondly, because of the importance of the questions developed from concepts and criteria traditionally used in education and, specifically, in terms of citizenship education (citizenship, participation, politics, etc.). Method: It is a qualitative and theoretical-conceptual work guided by the principles of documentary research (revision of educational laws) that aims to create new debates regarding the political problems that revolve around prospective citizenship education. Strategies / information gathering: specialized literature (educational problem), as well as a review of critical theoretical perspectives (political problem) to address concrete efforts about what type of profile (ideal) of citizenship is intended to be built by means of specific educational plans. As we will see in this article, these plans and projects will be delimited, to a large extent, by supranational criteria (context of the problem). Conclusions: Everything seems to point to a plan to preserve "old" concepts such as modernity and progress, in favor of an authentic resurgence disguised as a "hypermodernity" subject to the new (economic) rules of progress and framed in citizenship formation (education).